(untitled) (Scientific journal of the Fergana State University, 2023)
This article covers the coverage of land-water relations in the Turkistan General-Governorship in the end of the 19th century and the beginning of the 20th century, as well as the history and activities of the "Dehqan" magazine of the Turkestan Agriculture and State Property Department. The national economy of Turkistan is covered in the press and the role of agriculture in the lifestyle of the population is shown. The varieties of cotton planted in the fields, horticulture and horticulture were discussed.